Penerapan Arsitektur Perilaku yang Mendukung Perkembangan Psikososial Anak di Panti Asuhan Don Bosco Surabaya - Fanisa Aryantika Amanda Putri; Yusvika Ratri Harmunisa (Universitas Medan Area, 2026)
Abandoned children in orphanages often face challenges in meeting their psychological and physical needs, which can impact their overall development. Currently, there is still a gap in environmental design that can meet the specific needs of children. Orphanages are a crucial environment for the development of disadvantaged children, where behavioral architecture approach can be one of the solutions to support their psychosocial development. This study aims to examine the application of behavioral architecture to the psychosocial development of children in orphanages. The research method used is a descriptive case study with a qualitative approach. Data collection was carried out through direct observation at the orphanage, in-depth interviews with staff, and analysis of documents related to the architectural design of the orphanage. The results show that the application of behavioral architecture approach in the orphanage has not fully met the expected parameters. Although there are some positive aspects, such as increased sense of comfort and security among children in the orphanage space, the room design has not fully suited the age and character of the children. Many rooms require adjustments to meet the specific needs of children, such as more flexible and adaptive spaces to support the development of their creativity, social interaction, and privacy. Therefore, further improvement and adjustment are needed to achieve an ideal orphanage environment for children.